Safety of Tenofovir Disoproxil Fumarate for Pregnant Women Facing the Coronavirus Disease 2019 Pandemic. Issue 11 (13th April 2021) - Hernández-Díaz, Sonia; Bateman, Brian T; Straub, Loreen; Zhu, Yanmin; Mogun, Helen; Fischer, Michael; Huybrechts, Krista F
Abstract: We assessed the teratogenicity of tenofovir, a human immunodeficiency virus (HIV) drug similar to remdesivir that is currently being evaluated for the treatment of coronavirus disease 2019 (COVID-19). Using US Medicaid Analytic eXtract (MAX) claims data (2000–2014), we identified a population-based pregnancy cohort of women with HIV who filled at least 1 prescription for antiretroviral therapies (ART) during the first trimester. Women on tenofovir disoproxil fumarate (TDF) were compared with women receiving ART without TDF. Major malformations were identified by International Classification of Diseases, Ninth Revision, codes using validated algorithms. Relative risks and 95% confidence intervals were estimated using propensity score stratification to control for potential confounders. We incorporated the results into prior knowledge by conducting a systematic literature review and a meta-analysis. Major congenital malformations were diagnosed in 37 out of 866 (4.27%) infants exposed to TDF and 38 out of 1, 020 (3.73%) infants exposed to ART other than TDF; the adjusted relative risk was 1.21 (95% confidence interval: 0.77, 1.90). Estimates for specific malformations were imprecise. The pooled relative risk from the meta-analysis with 6 prior studies was 0.88 (95% confidence interval: 0.75, 1.03). Based on evidence accumulated in patients with HIV, first-trimester TDF use does not increase the risk of major congenital malformations overall in the newborn compared with other ART.